Speak no evil [videorecording (Blu-Ray)] - Watkins, James, 1978-; McAvoy, James, 1979-; Davis, Mackenzie; Franciosi, Aisling, 1993-; Lefler, Alix West; Hough, Dan, (Actor); Hitchen, Kris, 1974-; McNairy, Scoot; Bensi, Danny; Jurriaans, Saunder; Maurice-Jones, Tim (Universal, 2024)
When an American family is invited to spend the weekend at the idyllic country estate of a charming British family they befriended on vacation, what begins as a dream holiday soon warps into a snarled psychological nightmare.